2012
DOI: 10.1016/j.bmcl.2012.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Design and optimization of quinazoline derivatives as melanin concentrating hormone receptor 1 (MCHR1) antagonists: Part 2

Abstract: Melanin concentrating hormone receptor 1 (MCHR1) antagonists have potential for the treatment of obesity and several CNS disorders. In the preceding article, we have described a novel series of quinazolines as MCHR1 antagonists and demonstrated in vivo proof of principle with an early lead. Herein we describe the detailed SAR and SPR studies to identify an optimized lead candidate having good efficacy in a sub-chronic DIO model with a good cardiovascular safety window.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Studies have shown that Quinazoline and its derivatives, which belong to organic heterocyclic compounds, possess a broad range of biopharmaceutical activities, including anti-inflammation [ 19 ], antimicrobial [ 20 , 21 ], antimetabolic syndrome [ 22 , 23 , 24 ], anti-convulsant [ 25 , 26 ] and anti-psychotics activity [ 27 ]. In recent years, quinazoline derivatives have been developed as drugs against different tumors, including FDA-approved erlotinib, gefitinib, vandetanib and lapatinib [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Quinazoline and its derivatives, which belong to organic heterocyclic compounds, possess a broad range of biopharmaceutical activities, including anti-inflammation [ 19 ], antimicrobial [ 20 , 21 ], antimetabolic syndrome [ 22 , 23 , 24 ], anti-convulsant [ 25 , 26 ] and anti-psychotics activity [ 27 ]. In recent years, quinazoline derivatives have been developed as drugs against different tumors, including FDA-approved erlotinib, gefitinib, vandetanib and lapatinib [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of quinazoline derivatives ( 104 – 106 ) are to be considered as an antagonist for melanin concentrating hormone receptor 1 (MCHR1) [ 90 ] (see Scheme 71 ).…”
Section: Biological Importance Of Quinazoline Derivativesmentioning
confidence: 99%
“…Among these GW 856464 [211], AMG076 [212] and NGD-4715 [213] achieved phase 1 clinical investigations. Trials to optimize quinazolines [214][215][216][217][218][219], as (40) (Figure 9(a)), revealed GW 803430 (GW3430; [214]), ATC0175 and ATC0065 [215] which were shown efficacious in rodent depression models [197]. However, ATC0175 and ATC0065 are binding with high affinity not only to MCH1-R but also to subtypes of the 5 HT receptor [197] suggesting that the antidepressiv effect of the MCH1-R antagonist is not due to MCH1-R alone.…”
Section: Non-peptide Ligands Of Mch-receptorsmentioning
confidence: 99%